Scottish silver arm-rings: an analysis of weights (Proceedings of the Society of Antiquaries of Scotland, 1978)
The weights of seventy-two silver arm-rings or 'ring-money' from Scotland and the Isle of Man were analysed, and their weight distribution was tested to discover whether any target values were involved. Results gave a target of 24.0 + 0.8gm, equivalent to the Norwegian øre, but there appears to have been considerable flexibility in the manufacture of individual rings. A R. See 78/5592.